Protective effect of gel form of gastric gavage applicated aloe vera on ischemia reperfusion injury in renal and lung tissue - Sahin, Hasan; Yener, Ali Umit; Karaboga, Ihsan; Sehitoglu, Muserref Hilal; Dogu, Tugba; Altinisik, Hatice Betul; Altinisik, Ugur; Simsek, Tuncer (Cellular and Molecular Biology, 2017)
The aloe vera plant has become increasingly popular in recent years. This study aimed to research the effect of aloe vera to prevent renal and lung tissue damage in an experimental ischemia–reperfusion (I/R) injury model. The study included 21 male Wistar Albino rats, which were categorized into control group, n = 7 (no procedures), Sham group n = 7 (I/R); and aloe vera therapy group, n = 7 (aloe vera and I/R). Superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and malondialdehyde (MDA) were evaluated from lung and kidney tissues for biochemical investigations. As histopathological, hematoxylin and eosin and anti-iNOS were also examined. In biochemical investigations, SOD, CAT, and GPx levels of the Sham group were found to be lower compared with the other groups (P < 0.05). The aloe vera therapy group was not statistically different from control groups but significantly different compared with the Sham group. In the same way, the MDA levels of kidney and lung tissues were statistically significant in the aloe vera therapy group, compared to the Sham group. In the Sham group, the peribronchial and perialveolar edema were observed in lung parenchyma. Also, excess interstitial hemorrhage, leukocyte infiltration, and alveolar wall thickening were identified in ischemic groups. The histopathological changes were much lighter than in the aloe vera therapy group. In renal tissues, excess epithelial cell deterioration, tubular desqumination, and glomerular atrophy were observed in the Sham group. The histopathological changes were markedly reduced in the aloe vera therapy group. In the kidney and lung tissue, the level of iNOS activity in the Sham group was significantly higher than in the control and aloe vera therapy group. This study indicated that aloe vera is protective against oxidative damage formed by I/R in distant organs like the lungs and kidneys.